Dietary supplementation of Allium mongolicum modulates rumen-hindgut microbial community structure in Simmental calves - Xie, Kaili; Chang, Shenghua; Ning, Jiao; Guo, Yarong; Zhang, Cheng; Yan, Tianhai; Hou, Fujiang (Frontiers in Microbiology, 2023)
Compared to traditional herbage, functional native herbage is playing more important role in ruminant agriculture through improving digestion, metabolism and health of livestock; however, their effects on rumen microbial communities and hindgut fermentation are still not well understood. The objective of present study was to evaluate the effects of dietary addition of Allium mongolicum on bacterial communities in rumen and feces of claves. Sixteen 7-month-old male calves were randomly divided into four groups (n = 4). All calves were fed a basal ration containing roughage (alfalfa and oats) and mixed concentrate in a ratio of 60:40 on dry matter basis. In each group, the basal ration was supplemented with Allium mongolicum 0 (SL0), 200 (SL200), 400 (SL400), and 800 (SL800) mg/kg BW. The experiment lasted for 58 days. Rumen fluid and feces in rectum were collected, Rumen fluid and hindgut fecal were collected for analyzing bacterial community. In the rumen, Compared with SL0, there was a greater relative abundance of phylum Proteobacteria (p < 0.05) and genera Rikenellaceae_RC9_gut_group (p < 0.01) in SL800 treatment. In hindgut, compared with SL0, supplementation of A. mongolicum (SL200, SL400, or SL800) decreased in the relative abundances of Ruminococcaceae_UCG-014 (p < 0.01), Ruminiclostridium_5 (p < 0.01), Eubacterium_coprostanoligenes_group (p < 0.05), and Alistipes (p < 0.05) in feces; Whereas, the relative abundances of Christensenellaceae_R-7_group (p < 0.05), and Prevotella_1 (p < 0.01) in SL800 were higher in feces, to maintain hindgut stability. This study provided evidence that A. mongolicum affects the gastrointestinal of calves, by influencing microbiota in their rumen and feces.